Peran Bimbingan dan Konseling dalam Penguatan Pendidikan Karakter di Sekolah Menengah Kejuruan - Muslihati, Muslihati (Jurnal Kajian Bimbingan dan Konseling, 2019)
This research aims at describing the roles of guidance and counseling in strengthening character education of the students of Mitra Industri MM2100 Vocational High School, Cikarang, Bekasi, West Java. It used qualitative approach with case study design, in which the data was collected through interview and observation. The main informants were: coordinator of Mitra Industri Cikarang Foundation; principal; assistant principal of academic affairs and curriculum; dean of students; school counselor; homeroom teacher; and students of Mitra Industri MM2100 Vocational High School. The data was analyzed by category and reduction in accordance with the focus of the research. The results of the research show that guidance and counseling has important roles in strengthening the character education. guidance and counseling has active roles in the selection process; preventing deviant behaviors; and eradication of deviant behaviors in students. These roles are conducted collaboratively with the dean of students; homeroom teacher; parents; and students. The success of character education program in Vocational High School is determined by the establishment of the “golden triangle of communication” which is the common awareness and commitment between: school; parents; and students. In addition, daily and weekly evaluation and supervision allows the school, particularly guidance and counseling teacher to identify, anticipate and respond to the indication of behavior and character issues of the students in an appropriate manner. From the results of the research, the board of Vocational High School is recommended to develop a character education system collaboratively with school counselor; dean of students; parents; and students.